Delivery of transplant care among Hmong kidney transplant recipients: Outcomes from a single institution. Issue 5 (6th April 2019) - Odegard, Marjorie; Serrano, Oscar K.; Peterson, Kent; Mongin, Steven J.; Berglund, Danielle; Vock, David M.; Chinnakotla, Srinath; Dunn, Ty B.; Finger, Erik B.; Kandaswamy, Raja; Pruett, Timothy L.; Matas, Arthur J.
Abstract: Kidney transplantation entails well‐coordinated complex care delivery. Patient‐provider cultural and linguistic discordance can lead to healthcare disparities. We analyzed kidney transplantation outcomes among our institution's Hmong recipients using a retrospective cohort study. From 1995 to 2015, 2164 adult (age ≥18) recipients underwent kidney transplantation at our institution; 78 self‐identified as Hmong. Survival rates were analyzed and compared to Caucasian recipients (n = 2086). Fifty (64.1%) Hmong recipients consistently requested interpreters. Mean follow‐up was 9.8 years for both groups. Hmong recipients (N = 78) were on average younger at transplant (45.7 vs 49.7 years; P  = 0.02), more likely to be female (56% vs 38%; P  = 0.001), and had higher gravidity (5.0 vs 1.9 births; P  < 0.001). There were 13 (16.7%) Hmong living donor recipients, who were younger (32.8 vs 42.9 years; P  = 0.006) at transplant compared to Caucasians (1429, 68.5%). Hmong 1‐ and 5‐year patient survival was 100%; Caucasians, 97.1% and 88% ( P  < 0.001). Hmong 1‐ and 5‐year graft survival was 98.7% and 84.9%; Caucasians 94.8% and 80.9% ( P  = 0.013). One‐ and 5‐year rejection‐free survival showed no difference (88.9% vs 82.4%; 86.7% vs 83.4%, P  = 0.996). Despite cultural and linguistic differences between Hmong recipients and providers, we found no evidence of inferiority in KT outcomes in the Hmong population.